The effects of specialized probation and recovery management checkups (RMCs) on treatment participation, substance use, HIV risk behaviors, and recidivism among female offenders: main findings of a 3-year experiment using subject by intervention interaction analysis - Scott, Christy K. (Journal of experimental criminology, 2017)
To examine the effects of specialized probation and recovery management checkups (RMCs) on participation in substance use treatment, substance use, HIV risk behaviors, and recidivism.